Case Report: B20 Infection - Lina Nur Islamiyyah Yunus (Faculty of Medicine, Public Health, and Nursing, 2018)
.......The problem, in this case, was very complicated. We should pay attention to several aspects in the approach for HIV patients: privacy (respect patient's privacy), confidentiality (we must keep patient’s health information confidential), fidelity, and veracity (upholding truth and honesty). The confidentiality in this case was patient’s status as an HIV patient. Also, we must understand that the complaints experienced by HIV patients would be different from one and another.In addition to her physical problems, there was also her psychosocial problem. Assistances from an HIV counselor for the patient while maintaining her confidentiality were needed to manage the patient’s health problems, such as......